2007
DOI: 10.1590/s0101-81082007000300011
|View full text |Cite
|
Sign up to set email alerts
|

Impacto dos transtornos depressivos e ansiosos sobre as manifestações da menopausa

Abstract: ResumoObjetivo: Determinar, pela primeira vez, em uma amostra ambulatorial brasileira, o impacto dos diagnósticos psiquiátricos sobre os sintomas da menopausa presentes no índice de menopausa de Blatt-Kupperman (B-K). Métodos: Avaliamos consecutivamente, através do instrumento diagnóstico estruturado MINI 4.4 e da entrevista psiquiátrica tradicional, mulheres (n = 86) em atendimento no ambulatório de menopausa do Instituto de Ginecologia da Universidade Federal do Rio de Janeiro. As pacientes incluídas no estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Likewise, the prevalence of anxiety disorders and symptoms in our study resemble the rates found by other studies. Veras et al 24 found that 33.3% of peri- and postmenopausal Brazilian women were diagnosed with anxiety disorders according to the MINI, and the prevalence of anxiety symptoms reported by Polisseni et al 2 was 56.3%. Other studies, however, reported frequencies ranging from 9 to 21%, and these lower rates may be associated with broader inclusion criteria and the rating scales used.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, the prevalence of anxiety disorders and symptoms in our study resemble the rates found by other studies. Veras et al 24 found that 33.3% of peri- and postmenopausal Brazilian women were diagnosed with anxiety disorders according to the MINI, and the prevalence of anxiety symptoms reported by Polisseni et al 2 was 56.3%. Other studies, however, reported frequencies ranging from 9 to 21%, and these lower rates may be associated with broader inclusion criteria and the rating scales used.…”
Section: Discussionmentioning
confidence: 96%
“…In Brazilian studies with perimenopausal women, the prevalence of the diagnosis of depression has ranged from 18.7 to 34.3%, while the prevalence of depressive symptoms has been reported as 46.9%. 2,24,25 In a cross-sectional study of the SWAN cohort, 68.6% of perimenopausal women reported depressive symptoms. Likewise, the prevalence of anxiety disorders and symptoms in our study resemble the rates found by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[18] The association of depressive symptoms with advancing age is indeed consistent and grounded in the literature. [14,19] Menopause is a period marked by hormonal changes, which result in physical, psychological and social consequences. Therefore, it is a considerably stressful phase, and may lead to changes in mood and even depression.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, studies have shown that unemployment is predictive for the development of depressive symptoms. [17,19] Studies have reported that low family income can be an important factor in justifying increased rates of depression because it is connected to social conditions such as unemployment, low education, poor quality housing and inadequate food. Such conditions, exclusive or combined, favor the development of a hopeless state, which has the immediate effect of reducing the ability to handle stressful situations properly, reducing willingness to withstand adverse and frustrating events.…”
Section: Discussionmentioning
confidence: 99%
“…Ao observamos que o maior número de mulheres (194 -25,4%) encontrava-se com idade entre 41 a 50 anos, torna-se oportuno ressaltar que nesta faixa etária ocorre o climatério, que consiste no final da vida reprodutiva da mulher, onde se destacam alterações hormonais significativas, que em sua grande maioria resultam em sintomas físicos, psicológicos e sociais, configurando uma fase de considerável estresse e de maior vulnerabilidade psíquica da mulher (15)(16) .…”
Section: Discussionunclassified